Physiological Responses to Ocean Warming and Acidification of Diplodus cervinus - Carmona, Mariana Marques (2021)
Climate change is one of the main global environmental threats, especially in the marine biosphere. The increased ocean temperatures and low pH can induce the generation of oxygen reactive species (ROS) which are the primary source of damage to marine species, forcing them to activate response mechanisms that allows them to survive under environmental stress conditions. Nevertheless, the studies focused on the impacts of these stressors on marine organism’s physiological responses are still scarce and require further understanding. In this context, the main goals of the present work were to study, for the first time, the effects of ocean warming (+4 °C) and acidification (ΔpH=−0.4 units equivalent to ΔpCO2~1000μatm) on the antioxidant enzyme activities [superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), glutathione peroxidase (GPx) and total antioxidant capacity (TAC)], lipid peroxidation (LPO), acetylcholinesterase (AChE), heat shock response (HSP70) and ubiquitin content (Ub)], animal fitness [hepatosomatic index (HSI), viscerosomatic index (VSI) and Fulton’s condition index (K)] and haematological parameters (erythrocytes and leucocytes content) in different tissues (brain, muscle, liver and gills) of juvenile zebra seabream (Diplodus cervinus). Despite the distinct responses of each tissue to environmental stressors, the present study evidenced that fish antioxidant machinery and other mechanisms such as HSP70, Ub, AChE and LPO significantly responded to warming and acidification, acting alone or combined (e.g. CAT increased in liver and decreased in muscle; SOD activity is severely compromised and only significantly increases in the muscle when exposed to both stressors). The liver, being the main tissue responsible for ROS detoxification, revealed the highest expression for the measured biomarkers. Animal fitness was also significantly affected by warming, i.e. body weight increased, while HSI decreased. Haematological parameters showed that warming, alone or combined with acidification increases erythrocytes percentage and warming alone decreases the leucocytes percentage. Overall, the present findings demonstrated that the exposure to ocean warming and acidification may compromise the cellular adjustments and antioxidant responses of marine organisms and thus lead to physiological impairments.